Secondhand smoke exposure and other correlates of susceptibility to smoking: A propensity score matching approach. (September 2015) - McIntire, Russell K.; Nelson, Ashlyn A.; Macy, Jonathan T.; Seo, Dong-Chul; Kolbe, Lloyd J.
Abstract: Secondhand smoke (SHS) exposure is responsible for numerous diseases of the lungs and other bodily systems among children. In addition to the adverse health effects of SHS exposure, studies show that children exposed to SHS are more likely to smoke in adolescence. Susceptibility to smoking is a measure used to identify adolescent never-smokers who are at risk for smoking. Limited research has been conducted on the influence of SHS on susceptibility to smoking. The purpose of this study was to determine a robust measure of the strength of correlation between SHS exposure and susceptibility to smoking among never-smoking U.S. adolescents. This study used data from the 2009 National Youth Tobacco Survey to identify predictors of susceptibility to smoking in the full (pre-match) sample of adolescents and a smaller (post-match) sample created by propensity score matching. Results showed a significant association between SHS exposure and susceptibility to smoking among never-smoking adolescents in the pre-match (OR = 1.47) and post-match (OR = 1.52) samples. The odds ratio increase after matching suggests that the strength of the relationship was underestimated in the pre-match sample. Other significant correlates of susceptibility to smoking identified include: gender, race/ethnicity, personal income, smoke-free home rules, number of smoking friends, perception of SHS harm, perceived benefits of smoking, and exposure to pro-tobacco media messages. The use of propensity score matching procedures reduced bias in the post-match sample, and provided a more robust estimate of the influence of SHS exposure on susceptibility to smoking, compared to the pre-match sample estimates. Highlights: We test association of secondhand smoke and smoking susceptibility among adolescents. We use propensity score matching to reduce selection bias in sample. Secondhand smoke exposure predicts smoking susceptibility before and after matching. Odds ratio increase after matching suggests that pre-match estimates were biased. We find a robust estimate of secondhand smoke and smoking susceptibility association.